Recent progress in theoretical and computational investigations of structural stability and activity of single-atom electrocatalysts - Wang, Youwei; Song, Erhong; Qiu, Wujie; Zhao, Xiaolin; Zhou, Yao; Liu, Jianjun; Zhang, Wenqing (Progress in natural science, 2019)
This review has been made an attempt to seek some observed descriptors to comprehensively optimize structural stability and catalytic activity of single-atom catalysts. Electronic structure analysis can reveal the underlying mechanisms of atomic phy-chemical properties and local coordination structures on binding strength. The free electrons around Fermi level play an important role to determine the binding strength, which can be further influenced by electronegativity difference between single atom and nearby support atoms. This investigation can contribute to understanding the underlying mechanisms for the design of stable and active catalysts, and further provide a deep insight to the potential pathways in the research field of single-atom catalysts. [Display omitted] •Free electrons near Fermi level determine the stability and catalytic activity.•Bond strength between single atom and supports affects the structural stability.•Dangling bond near Fermi level of single atom provides the catalytic activity.